2019
DOI: 10.1097/md.0000000000016582
|View full text |Cite
|
Sign up to set email alerts
|

Posterior mediastinal neurilemmoma accompanied by intrapulmonary sequestration in the left lower lobe

Abstract: Rationale: The presence of a mediastinal neurilemmoma accompanied by intrapulmonary sequestration is a rare occurrence. The clinical symptoms of a neurilemmoma depend on the site of the tumor. Diagnosis of pulmonary sequestration mainly depends on the presence of aberrant feeding arteries. Patient concerns: A 78-year-old woman was admitted to our hospital with a mediastinal space-occupying lesion of 50 years. Computed tomography and magnetic resonance imaging showed 2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is estimated that 9% of all schwannomas occur in the mediastinum. [10] Fifty percent of neurogenic tumors of the mediastinum are schwannomas. [3] In our series, schwannomas represented 5% of all soft tissue tumors of the mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 9% of all schwannomas occur in the mediastinum. [10] Fifty percent of neurogenic tumors of the mediastinum are schwannomas. [3] In our series, schwannomas represented 5% of all soft tissue tumors of the mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…Less than 9% of all schwannomas occur in the mediastinum [ 3 , 4 , 11 ]. In their epidemiological analysis of 1005 primary mediastinal neoplasm cases, Szolkowska et al [ 4 ], found that only 5% of mediastinal neoplasms correspond to schwannomas.…”
Section: Main Textmentioning
confidence: 99%
“…Most intrathoracic neurogenic tumours originate in the posterior mediastinum and only 5.4% are in the chest wall. 1 Approximately 95% of the pleural dependent tumours are malignant, most of which present as a product of metastasis. Needless to say, benign pleural tumours are very unusual and, among them, schwannoma is much less frequent.…”
Section: Introductionmentioning
confidence: 99%